2022
DOI: 10.1093/oxfimm/iqac003
|View full text |Cite
|
Sign up to set email alerts
|

The past, current and future epidemiological dynamic of SARS-CoV-2

Abstract: SARS-CoV-2, the agent of the COVID-19 pandemic, emerged in late 2019 in China, and rapidly spread throughout the world to reach all continents. As the virus expanded in its novel human host, viral lineages diversified through the accumulation of around two mutations a month on average. Different viral lineages have replaced each other since the start of the pandemic, with the most successful Alpha, Delta and Omicron Variants of Concern (VoCs) sequentially sweeping through the world to reach high global prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 298 publications
2
31
0
Order By: Relevance
“…Interestingly, if Omicron infection is less associated with severe COVID-19, it was also shown to be more contagious than Delta infection (Syed et al 2022;Cui et al 2022); this explains why many deaths were still observed during the BA-1 and BA-2 waves, the low frequency of severe form being counterbalanced by the massive number of infections. This observation undermines the statements describing Omicron as a step of SARS-CoV-2 toward a more "banal" coronavirus (Balloux et al 2022;Callaway 2021;Gudina, Ali, et Froeschl 2022), such as 229E, NL63, OC43 and HKU1, and is an argument to maintain high During the second quarter of 2022, new Omicron subvariants, BA.4 and BA.5, progressively became predominant in Europe. Studies showed a decrease in the neutralisation activities of antibodies elicited by vaccination (Wang et al 2022) and of therapeutic monoclonal antibodies (Takashita et al 2022) toward them.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Interestingly, if Omicron infection is less associated with severe COVID-19, it was also shown to be more contagious than Delta infection (Syed et al 2022;Cui et al 2022); this explains why many deaths were still observed during the BA-1 and BA-2 waves, the low frequency of severe form being counterbalanced by the massive number of infections. This observation undermines the statements describing Omicron as a step of SARS-CoV-2 toward a more "banal" coronavirus (Balloux et al 2022;Callaway 2021;Gudina, Ali, et Froeschl 2022), such as 229E, NL63, OC43 and HKU1, and is an argument to maintain high During the second quarter of 2022, new Omicron subvariants, BA.4 and BA.5, progressively became predominant in Europe. Studies showed a decrease in the neutralisation activities of antibodies elicited by vaccination (Wang et al 2022) and of therapeutic monoclonal antibodies (Takashita et al 2022) toward them.…”
Section: Discussionmentioning
confidence: 81%
“…Interestingly, if Omicron infection is less associated with severe COVID-19, it was also shown to be more contagious than Delta infection (Syed et al 2022; Cui et al 2022); this explains why many deaths were still observed during the BA-1 and BA-2 waves, the low frequency of severe form being counterbalanced by the massive number of infections. This observation undermines the statements describing Omicron as a step of SARS-CoV-2 toward a more “banal” coronavirus (Balloux et al 2022; Callaway 2021; Gudina, Ali, et Froeschl 2022), such as 229E, NL63, OC43 and HKU1, and is an argument to maintain high vaccine coverage. Moreover, divalent mRNA vaccines have received market authorisation by the European medicines agency (EMA 2022 for Wuhan SARS-CoV-2 and Omicron BA.1 SARS-CoV-2 on 01/09/2022), and by the Food and Drug Administration (FDA) of the USA (FDA 2022 Wuhan SARS-CoV-2 and Omicron BA.4/5 on 31/08/2022); our results suggest that patients with risk factors for severe Covid-19 should not wait for such vaccines before receiving a boosting injection (such an injection being recommended 3 to 6 months after the previous one), as currently available vaccines, targeting the Wuhan SARS-CoV-2 viral sequence, still retain efficacy.…”
Section: Discussionmentioning
confidence: 85%
“…On the basis of their modeling, the authors deduced the retro-colonization of humans by this strain from an unidentified mammal that was initially infected by humans. This result was subsequently grounded by additional empirical data obtained by other researchers [ 120 , 121 , 122 ]. Within their model, Boeger et al proved the presence of host oscillations for SARS-CoV-2, one of the core elements of the SP’s theoretical framework.…”
Section: Instrument For Practical Research: Epidemiology Genetics Eco...mentioning
confidence: 65%
“…New variants of SARS-CoV-2 emerged sequentially, becoming the predominant strains during the pandemic. These variants have distinct ACE2 binding affinity, virulence, transmissibility and host immune responses [88][89][90][91][92][93][94][95][96][97][98][99][100] (Figure 1). Currently, the most pronounced risk factor for SARS-CoV-2 infection is the emergence of new variants or subvariants that are resistant to neutralizing antibodies and with higher transmissibility 101 .…”
Section: New Variants Of Concernsmentioning
confidence: 99%